Perencanaan Pembelajaran Berbasis Daring pada Desa Tertinggal, Terdepan, dan Terluar di Kabupaten Sumbawa Nusa Tenggara Barat - Syahir, Muhammad (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This Policy Paper reviews that learning in remote, outermost, and underdeveloped villages (3T) is hampered by accessibility issues. Accessibility is not only in terms of regional reach, but also economic, health, and environmental. The existence of accessibility that is considered severe has an impact on the quality of education which is categorized as weak. This problem is followed up by providing additional internet facilities to support information and communication facilities, but internet utilization has not been maximized. The purpose of this analysis is 1) to describe and analyze the problem of weaknesses in the use of internet technology as a learning tool, and 2) to analyze appropriate educational planning for remote villages. This analysis was conducted using a descriptive qualitative approach. The results of this analysis are 1) the use of the internet to support the learning process is considered not optimal due to the human resources of teachers and madrasah leaders who do not understand online learning, 2) the educational planning process is carried out as a solution to the weaknesses of implementation, namely by using synoptic theory and improving teacher pedagogical competence. The conclusion is that educational planning needs to be done to improve the output and outcome of the planned program.